2012
DOI: 10.1186/1471-2431-12-58
|View full text |Cite
|
Sign up to set email alerts
|

The impact of childhood acute rotavirus gastroenteritis on the parents’ quality of life: prospective observational study in European primary care medical practices

Abstract: BackgroundRotavirus (RV) is the commonest cause of acute gastroenteritis in infants and young children worldwide. A Quality of Life study was conducted in primary care in three European countries as part of a larger epidemiological study (SPRIK) to investigate the impact of paediatric rotavirus gastroenteritis (RVGE) on affected children and their parents.MethodsA self-administered questionnaire was linguistically validated in Spanish, Italian and Polish. The questionnaire was included in an observational mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
1
22
0
1
Order By: Relevance
“…In addition, few studies have used multiple assessments to measure the effect of an acute illness on QOL for the entire episode, as most studies assess HRQOL only at presentation to a health-care facility. The limited number of studies assessing the association between rotavirus illness and QOL from Europe, North America and Thailand have estimated HRQOL to range from 0.604 to 0.896 in children and 0.618 to 0.875 in parents, where 1 indicates no effect of illness 169,170 . The differences between locations might be due to variations in the tools used, the type of health-care facility available and cultural determinants regarding when children are taken to a health-care facility.…”
Section: Quality Of Lifementioning
confidence: 99%
“…In addition, few studies have used multiple assessments to measure the effect of an acute illness on QOL for the entire episode, as most studies assess HRQOL only at presentation to a health-care facility. The limited number of studies assessing the association between rotavirus illness and QOL from Europe, North America and Thailand have estimated HRQOL to range from 0.604 to 0.896 in children and 0.618 to 0.875 in parents, where 1 indicates no effect of illness 169,170 . The differences between locations might be due to variations in the tools used, the type of health-care facility available and cultural determinants regarding when children are taken to a health-care facility.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Of the studies dealing with bacterial meningitis in general, one dealt with pneumococcal and bacterial meningitis but excluded that caused by H. influenzae type B [24] and the other dealt with bacterial meningitis caused by any of the three pathogens mentioned [22]. In addition, we found four studies in rotavirus [27][28][29][30] and one in patients with varicella [31]. The five meningitis studies identified all dealt with the impact of postmeningitis sequelae on QOL.…”
Section: Resultsmentioning
confidence: 99%
“…Of all the instruments identified, only one disease-specific instrument (the Child Acute Gastroenteritis Questionnaire/Parent Acute Gastroenteritis Questionnaire for acute gastroenteritis) specifically explored domains that were relevant to children and parents separately. Of the other instruments specific to the conditions of interest, some were designed to elicit responses from parents [27,29], whereas others appear to have been primarily designed for adults and then applied in populations younger than 18 years [16,17,19]. At least one of the scales could be described as being an ad hoc, study-specific measure [27].…”
Section: Resultsmentioning
confidence: 99%
“…A multi-country study in Europe by Domingo at al. assessing the impact of RGE on the parents [ 21 ] described the highest impact among parents of children aged 12–23 months, mostly concerning symptoms and daily activities, with little difference among the countries.…”
Section: Discussionmentioning
confidence: 99%